Language template. The joint functioning of transmitting and influencing language elements in mass media language - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2025)
The formation of language templates is characteristic of mass communication means. Their usage in mass media language is conditioned by the need to optimize communication and intensify influence. They participate in the simultaneous activation of transmitting and influencing elements. The combination of these elements not only ensures the transfer of information but also aims to shape clear attitudes and exert influence. The linguistic template is primarily a communicative component, while the influencing element is one of persuasion.            The analysis shows that the combination of transmitting and influencing elements is a systemic feature of mass media language, most noticeable in genres where information is accompanied by commentary, evaluation, or exhortation. The template, as a linguistic unit, in this context becomes not only a formal component but also a carrier of influence, ensuring the structural and semantic integrity of media communication.
Keywords: language template; general language template; media-language template; speech formulas; extralinguistic factors; linguistic-cognitive factors; transmitting and influencing language elements; domain of use; functions